Study on the Formation Mechanism of Fish-Scale Defects during Flow Forming of Copper Alloy Tubes with Large Thickness-to-Diameter Ratio - Xia Qinxiang; Zhao Jie; Xiao Gangfeng; Tang Delin; Cui Huachun (MATEC Web of Conferences)
Flow forming is one of the most effective methods for producing tube-shaped parts. However, fish-scale defects occur easily during the flow forming of copper alloy tubes with large thickness-to-diameter ratio, which significantly affects the surface quality and performance of the spun tubes. The reason for the formation of fish-scale defects and the microstructural characteristics in the defective regions were investigated experimentally, the deformation behavior and strain distribution of materials were revealed through finite element simulation. The results show that fish-scale defects are a folding phenomenon caused by local instability during forming; deformation concentrates on the outer surface due to the large thickness-to-diameter ratio of the tubular blank and the low hardening index of the copper alloy; the plastic deformation ability of the material on the outer surface decreases with the increasing of deformation degree, which leads to local flow instability and results in the formation of fish-scale defects.